Rehabilitasi Bantaran Sungai melalui Penanaman Ketapang Kencana dan Ketapang Laut di Kelurahan Lubuk Kebur, Kabupaten Seluma - Demaslia Maura Farazhanty Syabirin; Maria Engela Sitorus; Ningrum Widya Rianti; Sheisa Putri Faisal; Yolanda Fitri Windia; Fachri Faisal (Al-DYAS, 2026)
The condition of the riverbanks in Lubuk Kebur Urban Village, Seluma Regency, Bengkulu Province, indicates limited shade vegetation along several sections of the banks and river transition zones, potentially increasing vulnerability to erosion and reducing aquatic environmental quality. Vegetation rehabilitation is necessary to strengthen the ecological functions of the riverbanks while increasing community involvement in maintaining ecosystem sustainability. This community service initiative aimed to rehabilitate riverbank vegetation by planting Madagascar almond (Terminalia mantaly) and tropical almond (Terminalia catappa) and to analyze the implementation of community participation-based greening as an effort to support aquatic ecosystem conservation and the achievement of SDG 14 (Life Below Water). The initiative employed a descriptive qualitative approach with a Participatory Action Research (PAR) scheme encompassing the planning, action, and reflection stages. Data were collected through field observations, activity documentation, and a literature review and were subsequently analyzed using qualitative descriptive methods through data reduction, data presentation, and conclusion drawing. The results showed that of the 110 seedlings managed, 10 Madagascar almond seedlings were planted directly by the Kuliah Kerja Nyata team at critical points along the riverbanks, while 100 tropical almond seedlings were distributed to 100 heads of households who owned land directly adjacent to the river for independent planting and maintenance. Community members actively participated in receiving, planting, and maintaining the distributed seedlings. The combination of direct planting and participatory seedling distribution expanded the coverage of vegetation rehabilitation while fostering a sense of community ownership and responsibility for riverbank conservation. These findings confirm that planting Madagascar almond and tropical almond trees can serve as a form of community-based conservation action that supports the sustainable restoration of riverbank ecological functions.